Electrolytic treatment of wastewater from a fowl slaughterhouse using cast-iron electrodes - Marconato, Jose Carlos [UNESP] (1998)
A viability study of an electrolytic process for the transformation of organic matter and free sulphide contained in wastewater from a fowl slaughterhouse in order to minimise odours was carried out Cast iron and aluminium electrodes were tried at 7.09 mA/cm2, under strong agitation, at 297 K. Conductivity, pH, chemical oxygen demand (COD), amount of settleable solids, and sulphide content were monitored with electrolysis duration. The cast iron electrodes were found to be viable for the elimination of soluble sulphides in the wastewater, leading to the elimination of its strong odour after short times of electrolysis. A significant decrease in COD was also attained.